Transaksi Sende Ditinjau Dari Maqâsid Al-Shâri’ah Al-Shâtibî (Studi di Desa Rejoagung Kecamatan Ngoro Kabupaten Jombang) - Hanik Latifah (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2017)
Transaction sende although the customary law sende transactions undertaken by some villagers Rejoagung have legitimate and has a strong legal evidence, but in the view of Islamic law the transaction is still experiencing some legal details. First, the transaction is a legitimate legal origin of the agreement is not in the contract or in the assembly khiyar. And for the buyer is obliged to keep promises. Buying and selling is called bai 'al-uhdah or selling by appointment. Second, if in the contract or in assemblies khiyar has stated that the agreement within a certain time the item will be repurchased or redeemed by the seller for the initial purchase and he as well as pledge or rahn. Akad pawn in Islam including accounts payable contract but was later accompanied by collateral that people who owed trust to give debt, because of the items that can be used as collateral for the repayment of debt. the results of the study as follows; First, sende transactions are often carried villagers Rejoagung District of Ngoro is a transaction that has become customary in the lives of the citizens of this transaction become the top choice of citizens to meet urgent needs in their muamalah activities. The main factor which encourages people to do this sende transactions, for the land owners is the need for money to do business and the urgent need for the recipient sende As is the advantage to manage the fields without losing money to buy or rent it. By most villagers Rejoagung, sende transaction is not a thing that gives problems for the economy of the families of both parties. Instead, this transaction provides many benefits to the economic needs of both parties. Second, In the concept maqashid al-shari'ah al-Syatibi, sende transaction is one that is diruriyah muamalah and hajiyah in its role as an effort to help meet the maintenance of property (hifzul-mal) and (hifz al-nafs). The existence of these transactions is very important for the village residents muamalah Rejoagung in running their activities. As muamalah transaction, this transaction is contained in some of the benefit and damage